Implementasi Peta Digital dalam Pesebaran Budaya di Setiap Provinsi Indonesia - Sayyida, Aulia Afifa; Melyana, Resty (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2024)
This study aims to develop and validate learning media in the form of a Google Earth-based digital map that illustrates the distribution of culture in each province in Indonesia. This media is designed to support interactive learning in the Pancasila and Citizenship Education (PPKn) subject at the elementary school level. Media development follows the ADDIE model which consists of the stages of analysis, design, development, implementation, and evaluation. Validation is carried out through a questionnaire that assesses three main aspects, namely material, media, and language. A total of 14 students were involved as validators, with an average validation score of 90% for the material aspect, 89% for the media aspect, and 90% for the language aspect, all of which are in the